2017
DOI: 10.1136/tsaco-2017-000126
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of mortality after colectomy in ischemic colitis: an ACS-NSQIP database study

Abstract: BackgroundSurgical intervention for ischemic colitis is associated with significant postoperative morbidity and mortality. Predictive factors of adverse outcomes have been reported in the literature, but are based on small sample populations. We sought to identify risk factors for mortality after emergent colectomy for ischemic colitis using a clinical outcomes database.MethodsThe American College of Surgeons National Surgical Quality Improvement Project database was queried from 2010 to 2015 to identify emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Acute colonic ischemia is known to be the most common indication for emergency digestive surgery in ESRD patients, representing around 45% of surgical indications as in the present study [9,13]. In general population, acute colonic ischemia is associated with a high postoperative mortality ranging from 25% to 37% [5,14,15]. Colonic ischemia is more prevalent in ESRD patient due to accelerated atherogenesis on one hand and hemodynamic changes and volume shift during dialysis on the other hand [5,16,17].…”
Section: Discussionmentioning
confidence: 53%
“…Acute colonic ischemia is known to be the most common indication for emergency digestive surgery in ESRD patients, representing around 45% of surgical indications as in the present study [9,13]. In general population, acute colonic ischemia is associated with a high postoperative mortality ranging from 25% to 37% [5,14,15]. Colonic ischemia is more prevalent in ESRD patient due to accelerated atherogenesis on one hand and hemodynamic changes and volume shift during dialysis on the other hand [5,16,17].…”
Section: Discussionmentioning
confidence: 53%
“…We found that CHF increases the risk of undergoing colectomy in hospitalized patients with IC. Moreover, patients undergoing colectomy due to complications of IC face higher perioperative mortality with a co-diagnosis of CHF [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The latter is one of the important factors affecting the healing process [3]. Ischemia in the anastomosis may occur due to arteriosclerotic vascular disease, advanced age, inflammatory vascular disease, vasoconstrictor drug use, and vascular network damage during the surgical manipulation [4,5].…”
Section: Introductionmentioning
confidence: 99%